Dimensioning Studies for Reversible Hydro Power Plants in Portuguese Islands - Manuel Matos (2018)
This work is within the scope of set of consultancy studies made for Portuguese islands. It focuses on the integration of Pumped Storage Power in isolated islands. The paper starts to address several power systems circumstances about two Portuguese islands on the energetic level. For each of these islands, an independent examination of the conditions to install a reversible hydro power plant is accomplished. Therefore, the energy volume to be stored due to excess of renewable generation and the ideal power and number of the pumps and turbines to be installed were identified and evaluated for the sake of using the produced energy surplus as to be pumped and later generated. The paper enhances the importance of storing energy in the operation of isolated and small systems with considerable amount of intermittent power resources as well as the conditions for the viability of installing new exploitations of this kind.